Timing of Palaeoproterozoic intra-orogenic sedimentation in the central Fennoscandian Shield; evidence from detrital zircon in metasandstone - Bergman, S; Högdahl, Karin; Nironen, M; Ogenhall, E; Sjostrom, H; Lundqvist, L; Lahtinen, R (Precambrian Research, 2008)
Detrital zircon U-Pb SIMS data on quartz-rich metasandstone units presumed to belong to the upper part of the Svecofennian stratigraphy in southeastern Finland and east-central Sweden suggest the existence of clastic sedimentary basins between the two main orogenic phases at 1.89-1.86 Ga and 1.83-1.79 Ga, during a period referred to as the intra-orogenic phase (1.86-1.83 Ga). Stratigraphically below the metasandstone at Hamrange, east-central Sweden, is a metadacite with an U-Pb zircon TIMS age of 1888 +/- 6 Ma, which indicates the maximum age of sedimentation. It also indicates that an earlier proposed correlation of Hamrange metavolcanic rocks and 1.86Ga equivalents at Los to the northwest must be rejected. Instead, there is a temporal affinity to the metavolcanic rocks in the Bergslagen Province to the south or Southern Finland to the east. Quartz-rich metasandstone samples from four localities, Luukkola, Pyhantaka and Tiirismaa in Finland and Hamrange in Sweden, yield multimodal detrital zircon age distributions with main populations at 2.95-2.60 Ga, 2.10-1.95 Ga and 1.92-1.85 Ga. The groups are similar in all four samples, and they are comparable to previously reported detrital ages in this part of the Fennoscandian Shield. The oldest zircon analysed gave an age of 3.32 Ga (Tiirismaa). The maximum ages of sedimentation (and of subsequent deformation and metamorphism), indicated by the youngest detrital zircon, from the four localities are 1842 10 Ma (Luukkola), 1865 +/- 11 Ma (Pyhantaka), 1848 +/- 13 Ma (Tiirismaa), and 1855 10 Ma (Hamrange), respectively. Possible source rocks for these zircon grains are found within and around the vast Ljusdal Batholith in Sweden, and in the Arc Complexes of Western and Southern Finland. It is concluded that several intra-orogenic sedimentary basins existed during the time interval 1.86-1.83 Ga ago, between two major orogenic events in the Fermoscandian Shield.